Influence of the concentration of H₂–D₂ mixtures on their triple-point dewetting behavior - Tibus, Stefan; Sohaili, Masoud; Klier, Jürgen; Leiderer, Paul (Физика низких температур, 2003)
Triple-point dewetting of pure gases like hydrogen and deuterium on solid substrates is a well-known phenomenon. This property persists even for the mixed system of H₂ and D₂. There exists an effective triple-point temperature T₃⁽mix⁾ , between the T₃ of pure H₂ and the one of pure D₂, which depends on the species concentrations. We present new investigations for a wide range of H₂–D₂ concentrations measured under different thermodynamic conditions. This allows us to map out T₃⁽mix⁾ as function of concentration, which can be different in the melting or solidifying direction. Furthermore, it turns out that the time the system needs to reach an equilibrium state can be very long and depends on concentration. This is not observed for the pure H₂ and D₂ system. Sometimes the relaxation times are so extremely long that significant hysteresis occurs during ramping the temperature, even if this is done very slowly on a scale of hours. This behavior can be understood on the basis of mixing and demixing processes. Possible differences in the species concentrations in the gas, liquid, and especially solid phase of the system are discussed. A preliminary phase diagram of the H₂–D₂ system is established.